Gut microbiota from essential tremor patients aggravates tremors in mice - Zhang, Ruo-Xin; Xu, Jia-Ting; Zhong, Hao-Jie; Cai, Ying-Li; Zhuang, Yu-Pei; Xie, Ya-Ting; He, Xing-Xiang (Frontiers in Microbiology, 2023)
Background and Objective: Essential tremor (ET) lacks effective treatments because its underlying mechanism is largely unknown, but may involve gut microbiota via the microbiome-gut-brain axis. We explored the effects of gut microbiota on ET in mice.Methods: Specific pathogen-free C57BL/6J mice were gavaged with stools from ET patients or matched healthy individuals. After 3 weeks of gavaging, behavioral tests were performed on all mice. Next, each mouse was injected with harmaline to induce tremors. The tremor duration was recorded; the tremor score was estimated every 30 min. Behavioral tests were repeated after modeling. Intestinal tissues and fecal samples of the mice were examined using histology and 16Sr DNA sequencing, respectively.Results: Compared with mice receiving microbiota from healthy controls, mice receiving fecal suspensions from ET patients showed worse performance in the premodeling behavioral tests. After modeling, ET-group mice showed significantly greater tremor scores, longer tremor duration, and worse motor performance. They also had significantly lower body weight and lower fecal pellet count. Pathological scoring revealed more severe intestinal lesions in ET-group mice. The 16S rDNA sequencing data revealed significant differences in microbiota indices, and a correlation between these indices and tremors in mice. Functional predictions indicated that the abundance of GABA-related enzymes was altered in ET-group mice.Conclusions: Mice transplanted with gut microbiota from ET patients showed worse 3 performance in behavioral tests. After modeling, ET-group mice presented longer tremor duration, higher tremor score, and worse motor performance. This study provides evidence for gut microbiota dysbiosis that may affect the pathogenesis of ET.